NEW REPORT OF ASPERGILLUS AWAMORI FRUIT ROT OF GUAVA IN PAKISTAN - N. Akhtar; K. Hanif; M. Shafiq; W. Anwar (Journal of Animal and Plant Sciences, 2018)
Rotting of guava fruits, selling in local fruit markets of three districts of Punjab, Pakistan i.e. Lahore, Shiekhupura and Kasur was observed in September 2014. Isolation and identification of causal organism was carried out from the diseased fruits. Aspergillus awamori was identified based on morphological characters. Identification was further verified by nucleotide sequence analysis of ITS region of rDNA and partial calmodulin gene. Phyylogenetic analysis of amplified ITS and partial calmodulin gene nucleotide sequences clearly showed that A. awamori is a distinct species within black Aspergilli group and present in the A. niger clade. Finally, after confirmation of pathogenicity, A. awamori was reported for the first time as a guava fruit rot pathogen from Pakistan. Guava (Psidium guajava) is a nutrient rich and out as described by Nayab and Akhtar (2016). Detail of unique flavored fiber fruit which is consumed fresh as primers used in present study is provided in Table 1. well as in processed form (Jams, beverages, ice cream Good quality amplified DNA fragments were sent for etc). This fruit contains vitamins; A, B6, C, thiamine and nucleotide sequencing. Resulting DNA sequences were riboflavin as well as essential minerals for example analysed by nucleotide BLAST. calcium, magnesium, potassium, iron and phosphorus. Phylogenetic analysis of nucleotide sequence Being naturally rich in vitamin C, guava has antioxidant data of amplified ITS region of the rDNA and partial properties which are helpful in prevention and cure of calmodulin gene was carried out (Varga et al., 2007; many diseases ( Chen and Yen, 2007; Joseph et al., 2011). Noonim et al., 2008; Varga et al., 2011). In September 2014, during a survey conducted to local For the completion of Koch's postulates, healthy fruit market of Lahore, Pakistan, guava fruits covered guava fruit were first surface sterilized and then with white mycelium and abundant dark brown conidia inoculated with the spores of isolated pathogen. Under were observed (Fig. 1A). Guava fruits showing the same aseptic conditions, five healthy fruits were first wounded symptoms were also collected from Shiekhupura and at three different points with the help of a sterilized 5 Kasur. Infected fruits from all the three sampling sites needle and then 10 spores were injected in each wound. were brought to the laboratory for pathogen(s) Sterilized water was also injected to fruits to be served as identification. Pathogen was cultured and purified on control. All fruits were kept at 25 ± 2 °C in separate Malt Extract Agar (Dhingra and Sinclair, 1995) and covered plastic boxes containing moistened blotting Czapek Dox Agar medium (Raper and Fennell, 1965) . paper bedding. Fruits were observed regularly for fungal Seven days old pure fungus culture grown at 25 °C was growth. Experiment was repeated three times. After 48 used for the identification of pathogen. Initially purified hours of spore injection, all inoculated fruits exhibited the fungal pathogen was identified on the basis of same disease symptoms of decay with powdery black morphological and cultural characters (colony color, size, spores and white mycelium as found on the fruits zonation, presence of exudates and sclerotia etc). collected initially for pathogen identification. However Complete description of macroscopic (type of conidial control fruits remained asymptomatic. Consistently re- heads, aerial and submerged mycelium) and microscopic isolation of A. awamori from artificially inoculated fruits ( conidiophores, phialides, metulae, vesicles and conidia) fulfilled Koch's pathogenicity postulates. characters was made using stereoscope and calibrated Cultural studies were conducted on 7 days old compound microscope respectively (Raper and Fennell, pure culture. Three isolates were selected for detailed 1965 Pildain et al., 2008) . morphological studies. Colonies on MEA growing Identification of pathogen based on morphology rapidly reaching 4.5 - 5.0 cm in 7 days at 25± 2 °C was confirmed by nucleotide sequence analysis of without zonation, colony texture was velutinous to Internal Transcribe Spacer Sequence (ITS) and partial floccose white from center, dark brown to black in color calmodulin gene (CAL). Total genomic DNA of fungal and creamy yellow in reserve. Sclerotia were absent pathogen was extracted following the method of Akhtar while colonies on CZ had clear zones in culture and et al. ( 2014) and used for the amplification of selected relatively slow growing attained a diameter of 3 - 4 cm. genes ( White et al., 1990) . The PCR reaction was carried Abundant radial conidial heads were present. 1537
Keywords: Aspergillus; guava; phylogenetic analysis; rot.